Changing minds with clinical hypnosis narratives and discourse for a new health care paradigm - Sugarman, Laurence I.; Linden, Julie Hope; Brooks, Lee Warner (Routledge, 2020)
This book is a scientifically current, integrative, and practical guide for understanding clinical hypnosis and its place within a new health care paradigm. Blending four original short stories with a treatise, it alternates narrative prose with health science discourse to create a framework for embracing systemic emotional and relational elements that lie beyond diagnosis, medication, surgery, and psychotherapy. Following the stories of four characters, the authors establish an empirically-grounded conceptualization of the mind, then demonstrate how practical applications of therapeutic hypnosis can help readers use individual and family resources in health and healing. Clinicians will learn to improve their care by embracing emotional, relational, and narrative elements that powerfully affect health beyond diagnosis, medication, surgery, and psychotherapy. Further, health care educators and policy makers will find inspiration that enriches professional training